Impact of migration on transport and congestion - Tsang, Flavia; Rohr, Charlene (Technical report (Rand Corporation), 2011)
RAND Europe has been commissioned by the Migration Advisory Committee (MAC) to collate evidence on how migration is likely to impact transport networks and congestion. This study was comprised of two research phases: a literature review followed by empirical analysis. Through the targeted literature review, we mapped the state of knowledge on the travel behavior of migrants (including travel frequency, mode choice, home and work location) and the associated impacts on the transport network. Almost all of the existing evidence found was from outside the UK. In the second phase, we undertook empirical analyses using UK data to provide a quantitative understanding of UK migrants' specific travel behaviour and impacts. This study informed the UK Migration Advisory Committee's (MAC's) thinking on the social impacts of migration. It provides one of the first studies using UK data to provide an empirical evidence base about migrants' travel behaviour and impacts.